1998
DOI: 10.1177/004728759803600402
|View full text |Cite
|
Sign up to set email alerts
|

Market Segmentation of an International Cultural-Historical Event in Italy

Abstract: This study explores the existing markets of a unique annual event, the Spoleto Festival in Italy, that blends inter nationally well-known cultural exhibitions with historical settings. Behavioral, motivational, and demographic char acteristics of festival visitors were examined by using a posteriori market segmentation. Factor analysis was performed to determine the leading motivations for attending the international cultural-historical event, whereas cluster analysis was employed to identify groups of respond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
170
0
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 290 publications
(181 citation statements)
references
References 31 publications
5
170
0
6
Order By: Relevance
“…For example, some studies based at country, classical, traditional Scottish, or jazz music festivals noted that the majority of festival-goers were over 35 (Formica & Uysal, 1998;McMorland & Mactaggart, 2007;Oakes, 2010;and Pegg & Patterson, 2010). Other studies of ethnic, folk, or multi-genre music festivals have shown the majority of attendees to be below 35 ( Blešić et al, 2013;Bowen & Daniels, 2005;and Gelder & Robinson, 2009).…”
Section: Insert Table 1 Herementioning
confidence: 99%
“…For example, some studies based at country, classical, traditional Scottish, or jazz music festivals noted that the majority of festival-goers were over 35 (Formica & Uysal, 1998;McMorland & Mactaggart, 2007;Oakes, 2010;and Pegg & Patterson, 2010). Other studies of ethnic, folk, or multi-genre music festivals have shown the majority of attendees to be below 35 ( Blešić et al, 2013;Bowen & Daniels, 2005;and Gelder & Robinson, 2009).…”
Section: Insert Table 1 Herementioning
confidence: 99%
“…This typology could be used based on the many factors such as the tourist demographic variables , the characteristics of the tourist destination (Locker, 1992), behavioral factors (Formica et al, 1998), and traveling motives , (Cha, 1995). The typology of tourists based on the traveling motives could help the tourism planners and policy makers to identify and satisfy each market the segment needs and wants successfully.…”
Section: 1tourism Market Segmentationmentioning
confidence: 99%
“…Getz (1993) and Formica and Uysal (1998) showed that the economic gains from festivals can be substantial because festivals provide interesting activities and spending venues for both local people and tourists. Research of the local population attitudes was conducted on the territory of the municipalities of Sombor and Apatin that belong to the administrative district of the western Ba~ka.…”
Section: Literature Reviewmentioning
confidence: 99%